2009
DOI: 10.1097/aco.0b013e32831f1c65
|View full text |Cite
|
Sign up to set email alerts
|

Current aspects of perioperative fluid handling in vascular surgery

Abstract: The basis of fluid therapy in vascular surgery is a careful differential indication of the respective classes of preparations. A goal-directed approach might help to avoid hypovolaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 77 publications
0
5
1
2
Order By: Relevance
“…VL, but not ANH, was associated with elevation of ANP and shedding of sdc1 and hyaluronic acid [84]. The obvious recommendation, therefore, is to avoid volume loading as far as possible in favour of haemodilution to save blood for abetting any subsequent loss [84][85][86]. Interestingly, heparan sulphate concentrations were not increased in either protocol, a distinction to the changes noted in the study on CABG-linked release of ANP (see above).…”
Section: Figurementioning
confidence: 76%
“…VL, but not ANH, was associated with elevation of ANP and shedding of sdc1 and hyaluronic acid [84]. The obvious recommendation, therefore, is to avoid volume loading as far as possible in favour of haemodilution to save blood for abetting any subsequent loss [84][85][86]. Interestingly, heparan sulphate concentrations were not increased in either protocol, a distinction to the changes noted in the study on CABG-linked release of ANP (see above).…”
Section: Figurementioning
confidence: 76%
“…Although several studies have reported the effects of increased perfusion pressure by administration of vasopressors, such as norepinephrine or phenylephrine, for septic shock [15][16][17][18] and vasodilatory state after cardiac surgery, 19 we are not aware of any study investigating the effects of normalizing arterial blood pressure on intestinal microcirculation in the setting of elective abdominal surgery. However, this is an important question in the perioperative period because several recent studies 20 have suggested that perioperative fluid administration should be goal directed, resulting in more restrictive use of intravenous crystalloid fluids. Furthermore, the use of colloids should be restricted mainly to replace intraoperative blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the use of colloids should be restricted mainly to replace intraoperative blood loss. 20,21 Consequently, hypotension occurring after induction and during maintenance of general anesthesia without significant blood loss should be treated with vasoconstrictor agents.…”
Section: Discussionmentioning
confidence: 99%
“…[16]. Ungezielte Volumenboli nach einer "Trial-and-Error"-Methode sind insgesamt kritisch zu betrachten [17], da jeder Patient einen individuellen präoperativen Volumenstatus aufweist, der klinisch kaum einzuschätzen ist [18].…”
Section: Merkeunclassified